STRATEGI PENTAHELIX PADA PENDIDIKAN AGAMA ISLAM ANAK USIA DINI - Tanzil Mutaqin, Moh Fikri Tanzil; Fachmi, Teguh; Ratu (Geneologi PAI: Jurnal Pendidikan Agama Islam, 2022)
Various challenges and problems continue to approach every element of life, including in the realm of education. In the realm of education, especially those handling early childhood faced great challenges such as stunting problems, innovative learning models, distribution of rural and urban education, and equitable distribution of educators. Also on the other hand students at the pre-school education level are facing a short development task during the Golden Age. Problems and challenges that are present simultaneously need serious handling from various elements including in the context of Islamic education early childhood. This article explores the Petahelix strategy in Early Childhood Islamic Education with Systematic Reviews that process data from various research results, journals and other written documents related to the implementation of early childhood Islamic education throughout Indonesia. The results of the analysis present the idea of ​​the Pethelix strategy in the implementation of early childhood Islamic education. There are five elements in the pentahelix strategy including the government, academics, the industrial world, the community, and the mass media. The government with the task of making and implementing convergent policies, Akakdemisi conducts research based on the subject matter, the industrial world supports material needs, the community involved as implementers, and the mass media by building literacy construction to the general public.